2019
DOI: 10.3390/dj7030070
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, Clinical and Histomorphometric Comparison between Equine Bone Manufactured through Enzymatic Antigen-Elimination and Bovine Bone Made Non-Antigenic Using a High-Temperature Process in Post-Extractive Socket Grafting. A Comparative Retrospective Clinical Study

Abstract: Enzyme-deantigenic equine bone (EDEB) and anorganic bovine bone (ABB) are two xenografts made non-antigenic through different processing methods. This study aimed to characterize them for the presence of native bone collagen and other proteins and to compare their histomorphometric outcome when they were used to graft post-extractive sockets. The records of 46 patients treated with EDEB (n = 22) or ABB (n = 24) and followed-up for at least four months after delayed implant placement, were retrospectively colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 32 publications
6
25
2
Order By: Relevance
“…Altogether, these findings confirm that the biophysical features of AEB are in agreement with that of the xenogeneic bone substitutes treated with high temperature and already described in literature [ 42 ]. Thus, one can expect a similar effectiveness in the repair of bone defects.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Altogether, these findings confirm that the biophysical features of AEB are in agreement with that of the xenogeneic bone substitutes treated with high temperature and already described in literature [ 42 ]. Thus, one can expect a similar effectiveness in the repair of bone defects.…”
Section: Discussionsupporting
confidence: 91%
“…To confirm the chemical composition of AEB, FT-IR analysis was performed, showing the bands associated with the chemical group of hydroxyapatite. The data analyzed showed the presence of phosphate ions at 1019 cm −1 and of the carbonate group at 1418 cm −1 and 875 cm −1 , in agreement with the literature describing the heat treatment output of xenogeneic bone substitutes [ 42 ]. The same bands were detected for ABB.…”
Section: Discussionsupporting
confidence: 88%
“…Current published evidence on using PRGF in sinus augmentation does not answer the question if the mixture may accelerate bone formation in the early stages after grafting, and if, accordingly, implant insertion could be carried out earlier; this should be the subject of appropriately designed prospective studies. Such advantage might be of a certain importance when the bone substitute being grafted is known to undergo slow remodeling, as with anorganic bovine bone [18,19]. Concerning EDEB, previous findings [20] show that it already allows early bone formation, to such extent that NFB in biopsies collected 3-5 months after grafting is not significantly different from that of biopsies collected later, up to 12 months from grafting.…”
Section: Discussionmentioning
confidence: 95%
“…The measurement will be repeated at the mesial side, and the two will be averaged. The MBL will be calculated as the difference between this averaged value and that measured repeating the whole procedure on the corresponding immediate post-insertion intraoral radiograph 18). Concerning the few split-mouth studies published at present comparing anorganic bovine bone alone to its mixture with PRGF, Anitua et al [40] reported anecdotic data concerning two patients whose NFB, in their sinuses grafted with the mixture was similar to that observed, in other studies, when sinuses are grafted with anorganic bone alone and, surprisingly, it was much lower when anorganic bovine bone was grafted alone (21.4% vs. 8.4% and 28.4% vs. 8.2%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation